Anguilla anguilla ... - Çiçek, Erdoğan; Fricke, Ronald; Sungur, Sevil; Çapar, Osman Bahadir; Golani, Daniel (Zenodo, 2023)
Anguilla anguilla (Linnaeus, 1758) [N]—European eel; Tzlofach eyropi or europi Taxonomy. Original description: Muraena anguilla Linnaeus, 1758: 245 [Europe, Mediterranean Sea, Baltic Sea, northeastern Atlantic (original: “in Europa; maxima in lacu Cornachio Ferrariensi”); localities include Sweden; England; Belgium; Germany; Poland; France; Ferrara and Rome, Italy; Lesbos Island, Greece; Syria; no types known].—Israel synonyms: None.—Revisions: Ege (1939: 90).—Illustration: Kottelat & Freyhof (2007: 62, fig.). Status in Israel. First record from Israel by Lortet (1883: 179) and Tristram (1884: 177) as Anguilla vulgaris, and Spicer (1931); confirmed by Goren & Ortal (1999: 4).—Israel material: HUJ. Distribution and habitat. Distribution in Israel: Mediterranean watersheds.—Distribution in River Basin: 1- Western Basin, 2-Dead Sea Basin.—General distribution: Western Atlantic: larvae in Sargasso Sea and Gulf Stream; eastern Atlantic, Baltic Sea, North Sea, White Sea, Mediterranean Sea, Sea of Marmara, ... : Published as part of Çiçek, Erdoğan, Fricke, Ronald, Sungur, Sevil, Çapar, Osman Bahadir & Golani, Daniel, 2023, Freshwater fishes of Israel; a revised and updated annotated checklist- 2023, pp. 451-484 in Zootaxa 5369 (4) on page 455, DOI: 10.11646/zootaxa.5369.4.1, http://zenodo.org/record/10146651 ...